2022
DOI: 10.1002/slct.202201728
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Identification of Natural Product‐Like Compounds as Potential Antibacterial Agents Targeting FemC of Staphylococcus aureus: An in‐Silico Approach

Abstract: FemC is a methicillin resistance factor and regulates the synthesis of peptidoglycan in Staphylococcus aureus. Here, a set of natural product‐like compounds from Enamine and Selleckchem databases were screened at the active site of validated FemC model. Molecules that had interactions and good binding energies with protein were filtered by pharmacokinetic and ADMET properties. Molecular docking and molecular dynamics (MD) analysis displayed the identified molecules had stable and static interactions with FemC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…The Ramachandran plot of Rv1250 generated by PROCHECK showed that 89.9% of the amino acid residues are in the most favoured region, 9.4% in the additional allowed region, 0.6% in the generously allowed region and 0.1% in disallowed region as shown in Figure 2 . The results showed that no residues were in the outliners region and similar scores were stated by Dhankhar et al (2020) , Dalal and Kumari (2022) .…”
Section: Resultssupporting
confidence: 79%
“…The Ramachandran plot of Rv1250 generated by PROCHECK showed that 89.9% of the amino acid residues are in the most favoured region, 9.4% in the additional allowed region, 0.6% in the generously allowed region and 0.1% in disallowed region as shown in Figure 2 . The results showed that no residues were in the outliners region and similar scores were stated by Dhankhar et al (2020) , Dalal and Kumari (2022) .…”
Section: Resultssupporting
confidence: 79%
“…Overall, the fluctuation intensity remains below 2.0 Å except for some residues representing a loop in the enzyme (Figure 6(C and D)). All complexes had low RMSF Coulomb (electrostatic potential), and Lennard Jones (Pauli repulsion, and Hydrophobic/Van Der Waals attractions) [31] …”
Section: Resultsmentioning
confidence: 99%
“…All complexes had low RMSF Coulomb (electrostatic potential), and Lennard Jones (Pauli repulsion, and Hydrophobic/Van Der Waals attractions). [31]…”
Section: Root Mean Square Fluctuations (Rmsf)mentioning
confidence: 99%
“…Then, hydrogens were added; average charges were assigned using Kollman charges, and torsional degrees of freedom were detected using AutoDockTools (ADT). The docking grid was defined to include active site residues , D22, H72, and H143. The x , y , and z coordinates of the center of the docking grid were set to −1.867, 6.077, and 37.778, respectively.…”
Section: Methodsmentioning
confidence: 99%